The effectual process of business model innovation for seizing opportunities in frontier markets - Karami, Masoud; Baber, William W.; Ojala, Arto (Elsevier, 2022)
Business model innovation is crucial for small digital service providers when they move into frontier markets. This study applies effectuation theory to explain how these firms innovate their business models as a cognitive description of the structure and activities. We conducted 24 interviews over five years with key decision-makers from eight small digital service providers in Japan and Canada. Our findings reveal that effectual logic of control enables decision-makers to utilize their internal means and innovate their business models in the face of rapid changes to shape and seize new opportunities at the frontier market. Focusing on the opportunity side of changes, taking action, learning from the results of each action, and collaboration with important stakeholders are the most important factors in successful entry into a frontier market. Also, technology and human capital play an important part in taking control of the frontier market entry process. We contribute to business model innovation research by theorizing the managerial cognition as a microlevel factor in BMI research. We also contribute to practitioners’ understanding of their cognitive models and BMI.
Keywords: Business model innovation; Effectuation; Opportunity creation; Uncertainty; fi=Kansainvälinen liiketoiminta|en=International Business|